Trust framework on exploitation of humans as the weakest link in cybersecurity - Daudi, Morice (NASK–Państwowy Instytut Wydawniczy, 2024)
Article published by the NASK–Państwowy Instytut Wydawniczy in the Journal of Applied Cybersecurity & Internet Governance Volume 2, Issue 1, Pages 1-26